2018
DOI: 10.1016/j.juro.2017.12.067
|View full text |Cite
|
Sign up to set email alerts
|

Complications of Recognized and Unrecognized Iatrogenic Ureteral Injury at Time of Hysterectomy: A Population Based Analysis

Abstract: Iatrogenic ureteral injury increases the risk of hospital readmission and significant, potentially life threatening complications. Unrecognized ureteral injury markedly increases these risks, warranting a high level of suspicion for ureteral injury and a low threshold for diagnostic investigation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
96
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(98 citation statements)
references
References 14 publications
1
96
1
Order By: Relevance
“…TO THE EDITORS: In their recent paper, Tay et al 1 assert that uterine and fetal placental Doppler indices are significantly associated with measures of maternal cardiovascular function, and go on to state that classic descriptions of uterine and fetal Doppler changes being initiated by placental maldevelopment are a "less plausible explanation" for the pathogenesis of preeclampsia and fetal growth restriction (FGR) than are maternal cardiovascular changes. 1 This conclusion is not supported by the findings described in the paper. Furthermore, their hypothesis fails when applied to pregnancies characterized by high rates of preeclampsia, such as molar pregnancy or trisomy 13, or the case of twin pregnancies with discordance for fetal growth restriction and preeclampsia.…”
Section: Uterine and Fetal Placental Doppler Indices Are Associated Wcontrasting
confidence: 62%
See 2 more Smart Citations
“…TO THE EDITORS: In their recent paper, Tay et al 1 assert that uterine and fetal placental Doppler indices are significantly associated with measures of maternal cardiovascular function, and go on to state that classic descriptions of uterine and fetal Doppler changes being initiated by placental maldevelopment are a "less plausible explanation" for the pathogenesis of preeclampsia and fetal growth restriction (FGR) than are maternal cardiovascular changes. 1 This conclusion is not supported by the findings described in the paper. Furthermore, their hypothesis fails when applied to pregnancies characterized by high rates of preeclampsia, such as molar pregnancy or trisomy 13, or the case of twin pregnancies with discordance for fetal growth restriction and preeclampsia.…”
Section: Uterine and Fetal Placental Doppler Indices Are Associated Wcontrasting
confidence: 62%
“…TO THE EDITORS: We thank Professor Yagel for his observations. We report that uterine and fetal Doppler indices are associated with maternal cardiovascular function, 1 and have previously found that cardiovascular function prior to pregnancy in healthy women is associated with the development of preeclampsia or fetal growth restriction. 2 Although we do not discount a role for the placenta in these pathological processes, the question is whether cardiovascular function or placental maldevelopment initiates them.…”
Section: Uterine and Fetal Placental Doppler Indices Are Associated Wmentioning
confidence: 75%
See 1 more Smart Citation
“…Diagnosis during rehospitalization was assumed to include an initial CT scan with confirmatory retrograde pyelogram at the time of stent placement for non-operative management or operative repair. Estimates of subsequent fistula formation, rehospitalization, sepsis and percutaneous nephrostomy placement were incorporated into the model based on data from Blackwell et al (10). Adjusted odds ratios were converted to probability ratios where appropriate (11).…”
Section: Ureteral Injury Assumptionsmentioning
confidence: 99%
“…When not recognized intra‐operatively, IUI is difficult to identify, even with dedicated imaging techniques such as urographic‐phase scanners. Such cases of unrecognized IUI have significantly higher rates of sepsis, urinary fistulas and renal impairment, as well as 40% higher mortality ( P = 0.003) .…”
Section: Introductionmentioning
confidence: 99%